Improving Outpatient Infusion Clinic Wait Times at a Comprehensive Cancer Center. Issue 12 (December 2021) - Hashemi-Sadraei, Neda; Sasankan, Shenthol; Crozier, Nick; Tawfik, Bernard; Kittson, Ronald; Abernathy, Janet; Lauer, Richard; Dayao, Zoneddy
Abstract : PURPOSE: Many factors contribute to long wait times for patients on the day of their chemotherapy infusion appointments. Longer wait time leads to nonoptimal care, increased costs, and decreased patient satisfaction. We conducted a quality improvement project to reduce the infusion wait times at a Comprehensive Cancer Center. METHODS: A multidisciplinary working group of physicians, infusion center nurses, pharmacists, information technology analysts, the Chief Medical Officer, and patient advocates formed a working group. Wait times were analyzed, and the contributing factors to long wait time were identified. Plan-Do-Study-Act cycles were implemented and included labeling patients ready to treat earlier, loading premedications into the medication dispensing system, increasing the number of pharmacy staff, and improving communication using a secure messaging system. The outcome measure was time from patient appointment to initiation of first drug at the infusion center. The secondary outcome measure was patient wait time satisfaction on the basis of Press Ganey score. RESULTS: Postintervention, the mean time from appointment to initiation of first drug decreased 17.6 minutes ( P < .001; 95% CI, 16.3 to 18.9), from 58.1 minutes to 40.5 minutes (43.5% decrease). Patient wait time satisfaction score increased 8.9 points ( P < .001; 95% CI, 6.0 to 11.82), from 76.2 to 85.1 (11.7% increase). CONCLUSION: Exploring real-time data and using a classic quality improvement methodology allowed a Comprehensive Cancer Center to identify deficiencies and prevent delays in chemotherapy initiation. This significantly improved patient wait time and patient satisfaction.